Application of carbon nanofiber electrode material with high hydrogen evolution overpotential and high activity in vanadium battery
By using electrospinning technology in vanadium batteries, the high hydrogen analysis overpotential and high activity carbon nanofiber electrode materials are solved, and the battery performance and charge and discharge efficiency are improved. Reduced energy storage costs.
Patent Information
- Application Number
- CN202311660122.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2024-12-13
AI Technical Summary
The hydrogen evolution side reaction kinetics of existing vanadium battery negative electrode materials are slow, which limits the battery performance, and the specific surface area and electrochemical reaction active area are insufficient, which affects the battery's power density and energy storage cost.
The carbon nanofiber electrode material with high hydrogen analysis overpotential and high activity is prepared by electrospinning technology. By introducing bismuth ammonium citrate into the electrospinning precursor solution, the electrocatalytic activity is increased and the hydrogen evolution side reaction is inhibited, and the negative electrode reaction is enhanced. study.
It effectively improves the electrolyte utilization rate of vanadium batteries, narrows the difference in reaction kinetics of positive and negative electrodes, improves battery performance and charge and discharge efficiency, and reduces energy storage costs.
Smart Images

Figure CN119133478A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials and energy storage, and specifically relates to the application of a carbon nanofiber electrode material with high hydrogen evolution overpotential and high activity in a vanadium battery. Background Art
[0002] Renewable energy can effectively solve the problem of shortage of traditional fossil energy resources, but the intermittent and volatile nature of renewable energy makes it difficult to meet electricity demand. Large-scale energy storage technology is the key to achieving grid connection of new energy. Liquid flow battery, as an important large-scale energy storage technology, can effectively solve the problem of discontinuity and instability of renewable energy, and provide important support for the large-scale development of renewable energy and the adjustment and transformation of energy structure in my country.
[0003] The energy of redox flow batteries is determined by the concentration and volume of the electrolyte, while the power is determined by the size of the battery stack, thus achieving the decoupling of energy and power. In addition, it has the advantages of large capacity, flexible design, long cycle life, high safety, and freedom of site selection. These unique advantages make it one of the most suitable technologies for large-scale energy storage. The research and development of vanadium battery electrode materials is of great significance for improving battery power density and reducing energy storage costs. Through material performance improvement and design optimization, the battery operating current density can be increased, the power density can be increased, and thus the energy storage cost can be indirectly reduced. Studies have shown that the negative electrode reaction of vanadium batteries is a key factor limiting battery performance. The kinetics of the negative electrode reaction are slow and the hydrogen evolution side reaction is coupled with the reduction reaction of trivalent vanadium ions. Selecting a suitable negative electrode material to suppress the hydrogen evolution side reaction while improving the electrode reaction kinetics is the key to improving battery performance.
[0004] At present, the most widely used flow battery electrode materials are carbon felt (CF) and graphite felt (GF), which have the advantages of low cost, high conductivity and good stability, but their low specific surface area and low electrochemical reaction active area seriously limit the battery performance. In recent years, electrospinning technology with strong controllability, strong designability and simple operation has been widely used to regulate the microstructure of carbon fiber electrode materials to prepare high-performance flow battery electrode materials. Electrospun carbon nanofiber (ECNFs) electrodes have higher specific surface area and electrochemical activity than carbon felt electrodes. In addition, by introducing suitable catalysts into the precursor solution, the electrocatalytic performance of the material can be simply and effectively improved, and the electrode can be given specific functionality in a targeted manner, such as hydrogen evolution inhibition. Therefore, by introducing electrode materials with high activity for the electrochemical reaction of negative electrode vanadium ions and high hydrogen evolution overpotential for the hydrogen evolution side reaction into the electrospinning precursor solution, the negative electrode reaction process of the vanadium battery can be promoted to a certain extent, thereby improving the battery performance. Summary of the invention
[0005] In view of the bottleneck problem of porous electrode materials for liquid flow batteries, the present invention provides a vanadium battery negative electrode material with both high hydrogen evolution overpotential and high electrocatalytic activity by considering two aspects: improving the hydrogen evolution overpotential of the negative electrode material and enhancing the electrocatalytic activity for the electrochemical reaction of vanadium ions.
[0006] The technical solution adopted by the present invention is:
[0007] The invention discloses an application of a carbon nanofiber electrode material with both high hydrogen evolution overpotential and high activity in a vanadium battery. The carbon nanofiber electrode material with both high hydrogen evolution overpotential and high activity is used as a negative electrode material in an all-vanadium liquid flow battery.
[0008] Furthermore, in the above application, the method for preparing the carbon nanofiber electrode material having both high hydrogen evolution overpotential and high activity comprises the following steps:
[0009] 1) Bismuth ammonium citrate C6H 13 BiN2O7·H2O is dispersed in N,N-dimethylformamide DMF solution, and then polyacrylonitrile PAN and ammonium bismuth citrate C6H are added after being evenly dispersed. 13 The addition amount of BiN2O7·H2O and polyacrylonitrile PAN is 1:50 to 1:5 by mass, and the three are fully mixed and dissolved to obtain a polyacrylonitrile-based electrospinning precursor solution containing bismuth ammonium citrate;
[0010] 2) electrospinning the polyacrylonitrile-based electrospinning precursor solution containing ammonium bismuth citrate obtained in step 1) to collect polyacrylonitrile-based three-dimensional nanofiber precursors containing ammonium bismuth citrate;
[0011] 3) placing the polyacrylonitrile-based three-dimensional nanofiber precursor containing bismuth ammonium citrate obtained in step 2) between corundum plates, and placing it in a box-type furnace for pre-oxidation treatment to obtain polyacrylonitrile-based pre-oxidized fibers;
[0012] 4) The polyacrylonitrile-based pre-oxidized fibers obtained in step 3) are carbonized to obtain a carbon nanofiber electrode material having both high hydrogen evolution overpotential and high activity.
[0013] Furthermore, in the above application, in step 1), in the presence of ammonium bismuth citrate C6H 13 In the mixed solution of BiN2O7·H2O, polyacrylonitrile PAN and N,N-dimethylformamide DMF, the concentration of polyacrylonitrile PAN is 8-18 wt %.
[0014] Furthermore, in the above application, in step 1), the molecular weight of the polyacrylonitrile PAN is 50,000 to 150,000.
[0015] Furthermore, in the above application, in step 1), ammonium bismuth citrate C6H 13The mixed dissolution conditions of BiN2O7·H2O, polyacrylonitrile PAN and N,N-dimethylformamide DMF are controlled as follows: temperature is 60-90°C and magnetic stirring is performed for 6-12 hours.
[0016] Furthermore, in the above application, in step 2), the conditions for electrospinning are: the receiver roller speed is 100-300 r / min; the voltage is 16-25 kV; the receiving distance is 8-15 cm; the spinning temperature is 20-50°C; the spinning humidity is 20-60% RH; the push speed is 10-60 μL / min; and the spinning time is 1-10 h.
[0017] Furthermore, in the above application, in step 3), the pre-oxidation treatment conditions are: heat treatment at 240-350° C. for 0.5-3 h in an air atmosphere.
[0018] Furthermore, in the above application, in step 4), the carbonization treatment conditions are: heat treatment at 900-1200° C. for 1-5 hours in vacuum, nitrogen or inert atmosphere.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention utilizes the powerful designability of electrospinning technology. By introducing a single functional component, ammonium bismuth citrate, into the electrospinning precursor solution, the hydrogen evolution inhibitor - bismuth, and the electrocatalytic heteroatoms - nitrogen and oxygen can be introduced simultaneously. The method is simple, efficient, universal, and suitable for large-scale production.
[0021] 2. The electrode material prepared by the present invention contains bismuth, nitrogen and oxygen functional components at the same time, and has high catalytic activity for the electrochemical reaction of negative electrode vanadium ions, a large active area and a high overpotential for the hydrogen evolution side reaction. It can inhibit the hydrogen evolution side reaction while promoting the negative electrode reaction process. As a negative electrode material for vanadium batteries, it can effectively reduce the kinetic differences between the positive and negative electrode reactions of vanadium batteries, thereby improving the utilization rate of the electrolyte and improving the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Scanning electron microscope images of the plane of the blank polyacrylonitrile carbon nanofiber electrode material (ECNFs) prepared in Example 1 (a) and the plane of the carbon nanofiber electrode material (NBi@ECNFs) with high hydrogen evolution overpotential and high activity (b).
[0023] Figure 2 Cyclic voltammetry curves of blank polyacrylonitrile carbon nanofiber electrode material (ECNFs) prepared in Example 1 and carbon nanofiber electrode material with high hydrogen evolution overpotential and high activity (NBi@ECNFs) in 0.1M VOSO4+2M H2SO4 (scan rate: 5mV·s-1 )(a) and electrochemical impedance Nyquist curve (polarization voltage: -0.5 V) (b).
[0024] Figure 3 The single cell assembled with the carbon nanofiber electrode material (NBi@ECNFs) with high hydrogen evolution overpotential and high activity prepared in Example 1 was -2 The charge and discharge curves under different current densities (a) and the Coulombic efficiency CE, voltage efficiency VE and energy efficiency EE (b). DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0026] Example 1
[0027] (I) Preparation of carbon nanofiber electrode materials with high hydrogen evolution overpotential and high activity
[0028] 1) Preparation of polyacrylonitrile-based three-dimensional nanofiber precursors containing ammonium bismuth citrate
[0029] 2.26 g of ammonium bismuth citrate (C6H 13 BiN2O7·H2O), 12g of polyacrylonitrile (PAN) powder with a molecular weight of 150000 was dried and mixed with 88g of N,N-dimethylformamide (DMF) solution, and the three were magnetically stirred at 80°C for 12h until they were completely dissolved to obtain a polyacrylonitrile-based electrospinning precursor solution containing bismuth ammonium citrate.
[0030] The polyacrylonitrile-based electrospinning precursor solution containing ammonium bismuth citrate was loaded into a syringe and placed on a syringe pump, the pipeline was connected, and aluminum foil was attached to a stainless steel roller as a receiver to collect the polyacrylonitrile-based three-dimensional nanofiber precursor containing ammonium bismuth citrate. Electrospinning conditions: the receiver roller speed was 150r / min; the voltage was 20kV; the receiving distance was 13cm; the spinning temperature was 27℃; the spinning humidity was 30%RH; the push speed was 30μL / min; the spinning time was 2h.
[0031] 2) Preparation of carbon nanofiber electrode materials (NBi@ECNFs) with high hydrogen evolution overpotential and high activity
[0032] The prepared polyacrylonitrile-based three-dimensional nanofiber precursor containing ammonium bismuth citrate was placed between corundum plates and put into a box furnace for pre-oxidation treatment, that is, heat treatment at 280° C. for 60 minutes in an air atmosphere to obtain polyacrylonitrile-based pre-oxidized fibers.
[0033] The obtained polyacrylonitrile-based pre-oxidized fibers were carbonized by heat treatment at 1000°C for 120 min in a nitrogen atmosphere to obtain a carbon nanofiber electrode material with high hydrogen evolution overpotential and high activity, which was labeled NBi@ECNFs.
[0034] (II) Comparative Example - Preparation of Blank Polyacrylonitrile Carbon Nanofiber Electrode Material (ECNFs)
[0035] Electrospinning was performed using the electrospinning precursor solution prepared under the same conditions as in (I) except that no ammonium bismuth citrate was added, and the fiber precursor was collected using a stainless steel roller with aluminum foil as a receiver to obtain blank polyacrylonitrile carbon nanofiber precursor. The blank polyacrylonitrile carbon nanofiber precursor was heat-treated under the same pre-oxidation and carbonization conditions as in the preparation of NBi@ECNFs to obtain blank polyacrylonitrile carbon nanofiber electrode materials, which were labeled as (ECNFs).
[0036] (III) Testing
[0037] Figure 1 Scanning electron microscope images of the prepared blank polyacrylonitrile carbon nanofiber electrode material (ECNFs) (a) and the carbon nanofiber electrode material with high hydrogen evolution overpotential and high activity (b). Figure 1 As shown in (a): The fiber diameter of blank polyacrylonitrile carbon nanofiber electrode material (ECNFs) is about 190-210nm, while the fiber diameter distribution of carbon nanofiber electrode material (NBi@ECNFs) with high hydrogen evolution overpotential and high activity is more uniform and slightly smaller, about 170-190nm. This may be because the addition of bismuth ammonium citrate increases the conductivity of the precursor spinning solution, and the electric field effect is stronger, resulting in a smaller fiber diameter, and the spun nanofibers are more uniform and continuous.
[0038] Example 2 Electrochemical performance of carbon nanofiber electrode materials with high hydrogen evolution overpotential and high activity
[0039] 1) Cyclic voltammetry (CV) test and electrochemical impedance spectroscopy (EIS) test
[0040] Method: The electrochemical properties of the material were tested using a three-electrode system, with the carbon nanofiber electrode material (NBi@ECNFs) with high hydrogen evolution overpotential and high activity prepared in Example 1 and blank polyacrylonitrile carbon nanofiber electrode material (ECNFs) as working electrodes; a 232-type saturated calomel electrode as a reference electrode; a platinum sheet as an auxiliary electrode, and 0.1M VOSO4+2.0MH2SO4 as the electrolyte.
[0041] Figure 2(a) is the measured cyclic voltammetry (CV) curve. The reaction current of the electrode material (NBi@ECNFs) obtained by nitrogen-bismuth co-doping to the negative electrode vanadium ion redox couple is significantly greater than that of ECNFs, and the redox peak position difference is reduced, indicating that it has excellent electrochemical activity and electrochemical reversibility. This once again shows that the introduction of ammonium bismuth citrate as a functional component can achieve nitrogen-bismuth co-doping, which synergistically improves the electrochemical reaction activity and hydrogen evolution inhibition of the carbon fiber electrode material.
[0042] The electrochemical properties of the material were further studied by electrochemical impedance spectroscopy, with a polarization potential of -0.5 V. Figure 2 (b) shows the Nyquist curves measured on two electrode materials, ECNFs and NBi@ECNFs. The Nyquist spectra of the two materials contain a semicircle and a linear part, indicating that the electrochemical reaction of vanadium ions on the surface of each electrode is controlled by a mixture of charge transfer and diffusion processes, and NBi@ECNFs has a smaller semicircle, indicating that it has a lower charge transfer resistance, which is consistent with the CV test results.
[0043] 2) Battery charge and discharge test
[0044] Method: The carbon nanofiber electrode material (NBi@ECNFs) with high hydrogen evolution overpotential and high activity prepared in Example 1 was used as the negative electrode, and the blank polyacrylonitrile carbon nanofiber electrode material (ECNFs) was used as the positive electrode. The area of the working electrode was 2×2 cm 2 , Nafion 212 is an ion exchange membrane, 1.65MV 3.5+ +3.0M H2SO4 as electrolyte, assemble single cell. The charge and discharge cut-off voltages are 1.65V and 1.0V respectively. The charge and discharge curves and battery efficiency of the battery are shown in Figure 3 shown.
[0045] Figure 3 (a) shows the difference between ENCFs and NBi@ECNFs at 200 mA·cm -2 Compared with the charge and discharge performance of the batteries assembled under the conditions of NBi@ECNFs, the battery assembled with NBi@ECNFs has a lower charge voltage and a higher discharge voltage, and the charge and discharge curve is more stable. The results show that NBi@ECNFs exhibits a lower polarization overpotential, thus having better charge and discharge performance.
[0046] Figure 3 (b) shows the coulombic efficiency CE, voltage efficiency VE and energy efficiency EE of NBi@ECNFs at different current densities. The battery can still operate smoothly at high current density, and at 200 mA cm -2 The voltage efficiency and energy efficiency of the battery reached 82.63% and 79.82% respectively.
Claims
1. Application of a carbon nanofiber electrode material having both high hydrogen evolution overpotential and high activity in a vanadium battery, characterized in that: The carbon nanofiber electrode material having both high hydrogen evolution overpotential and high activity is used as a negative electrode material in an all-vanadium liquid flow battery.
2. The use according to claim 1, characterized in that The method for preparing the carbon nanofiber electrode material having both high hydrogen evolution overpotential and high activity comprises the following steps: 1) Bismuth ammonium citrate C6H 13 BiN2O7·H2O is dispersed in N,N-dimethylformamide DMF solution, and then polyacrylonitrile PAN and ammonium bismuth citrate C6H are added after being evenly dispersed. 13 The addition amount of BiN2O7·H2O and polyacrylonitrile PAN is 1:50 to 1:5 by mass, and the three are fully mixed and dissolved to obtain a polyacrylonitrile-based electrospinning precursor solution containing bismuth ammonium citrate; 2) electrospinning the polyacrylonitrile-based electrospinning precursor solution containing ammonium bismuth citrate obtained in step 1) to collect polyacrylonitrile-based three-dimensional nanofiber precursors containing ammonium bismuth citrate; 3) placing the polyacrylonitrile-based three-dimensional nanofiber precursor containing bismuth ammonium citrate obtained in step 2) between corundum plates, and placing it in a box-type furnace for pre-oxidation treatment to obtain polyacrylonitrile-based pre-oxidized fibers; 4) The polyacrylonitrile-based pre-oxidized fibers obtained in step 3) are carbonized to obtain a carbon nanofiber electrode material having both high hydrogen evolution overpotential and high activity.
3. The use according to claim 2, characterized in that: In step 1), in the presence of ammonium bismuth citrate C6H 13 In the mixed solution of BiN2O7·H2O, polyacrylonitrile PAN and N,N-dimethylformamide DMF, the concentration of polyacrylonitrile PAN is 8-18 wt %.
4. The use according to claim 2, characterized in that: In step 1), the molecular weight of the polyacrylonitrile PAN is 50,000 to 150,000.
5. The use according to claim 2, characterized in that: In step 1), ammonium bismuth citrate C6H 13 The mixed dissolution conditions of BiN2O7·H2O, polyacrylonitrile PAN and N,N-dimethylformamide DMF are controlled as follows: temperature is 60-90°C and magnetic stirring is performed for 6-12 hours.
6. The use according to claim 2, characterized in that: In step 2), the conditions for electrospinning are: the receiver roller speed is 100-300 r / min; the voltage is 16-25 kV; the receiving distance is 8-15 cm; the spinning temperature is 20-50° C.; the spinning humidity is 20-60% RH; the push speed is 10-60 μL / min; and the spinning time is 1-10 h.
7. The use according to claim 2, characterized in that: In step 3), the pre-oxidation treatment conditions are: heat treatment at 240-350° C. for 0.5-3 h in an air atmosphere.
8. The use according to claim 2, characterized in that: In step 4), the carbonization treatment is carried out under the following conditions: heat treatment at 900-1200° C. for 1-5 hours in vacuum, nitrogen or inert atmosphere.
